Parenting stress predictors in mothers of families at psychosocial risk - Ayala Nunes, Lara (2018)
In this study we analyzed the associations between parenting stress, parental sense of competence and the contribution of socio-demographical and psychological factors to the explanation of parenting stress. Participants were 80 Portuguese mothers, recipients of the child protection services. Results showed high levels of parenting stress, especially in unemployed mothers with adolescent children, and significant associations between parenting stress and perceived parental competences. Maternal role satisfaction and employment were the most robust factors on the explanation of parenting stress, predicting 37% of the variance.